First record of piscivory in ghost pipefishes (Teleostei, Solenostomidae) revealed by micro‐computed tomography - Graham Short; Kerryn Parkinson; Thomas J Peachey; Richard Smith; David Harasti (Journal of Fish Biology, 2026)
Ghost pipefishes (Solenostomidae) have been regarded as specialist crustacean feeders since the 1960s, an inference resting on two primary dietary accounts. We report the first documented evidence of piscivory in the family based on micro‐computed tomography (micro‐CT) examination of voucher specimens of Solenostomus snuffleupagus and S. cyanopterus . Two head‐first teleost prey, both identified as gobiids, were recovered from the holotype of S. snuffleupagus , and additional ichthyic remains were recovered from an S. cyanopterus specimen collected in 1952, indicating a solenostomid diet broader than previously recognized.

Status, habitat use, and gear-specific conservation of threatened seahorses: The first integrated assessment in Taiwan - Colin Kuo-Chang Wen; Mei Shuet Kong; Ting-Chun Kuo; Chia-Hao Chang; Chih-Yang Huang; Chih-Wei Chen; Graham A. Short; Nathan W. Price (Biological Conservation, 2026)

Solenostomus snuffleupagus sp. nov., a hairy ghost pipefish (Teleostei: Solenostomidae) from the Southwest Pacific, with an integrative comparison to S. paegnius - Graham Short; David Harasti (Journal of Fish Biology, 2026)
A new species of ghost pipefish, Solenostomus snuffleupagus sp. nov., is described from the Coral Sea based on specimens (18–34 mm SL) collected from coral reef habitats in Queensland, Australia. The species is diagnosed by the following combination of characters: abundant elongate integumentary filaments imparting a conspicuously shaggy appearance; 36 total vertebrae (vs. 32–34 in all congeners); compact body form with a short, deep pretrunk (11%–14% SL); sexually dimorphic supraoccipital crests (moderately elevated in females, strongly developed in males); and two modified anchor‐like ossicles spanning the pterygiophores in both soft dorsal and anal fins. Micro‐CT imaging reveals distinctive pretrunk ossicle configuration characterized by deep angular interspaces and absence of a ventral ossicle series. Mitochondrial COI sequences indicate an uncorrected p‐distance of 22.0% from the superficially similar S. paegnius , a species with which it has long been confused in museum collections and citizen science databases. Field observations document consistent association with dense filamentous red macroalgae, with body coloration closely matching host substrate. The species is currently known from the southwest Pacific, including northeastern Australia (Coral Sea), Papua New Guinea, New Caledonia, Fiji and Tonga, representing a southwestern Pacific distribution.

First photographic evidence of trunk brooding in the southern Australian pipefish Notiocampus ruber (Teleostei, Syngnathidae) - Graham Short; Andrew Trevor‐Jones (Journal of Fish Biology, 2026)
Photographic observations from Gamay (Botany Bay), New South Wales, provide the first empirical evidence of ventral trunk brooding in the endemic southern Australian Red Pipefish Notiocampus ruber Ramsay & Ogilby, 1886, a historically understudied species. Syngnathidae is divided into two major clades, trunk‐brooding Nerophinae and tail‐brooding Syngnathinae, a framework supported by molecular phylogenetic studies. The observations reported here support the placement of Notiocampus within Nerophinae and reveal shared characters with the northeastern Atlantic nerophine genera Nerophis and Entelurus . This morphological evidence resolves a persistent uncertainty and underscores the need to include Notiocampus in future phylogenomic studies of Nerophinae.

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

An analogous scale model for laboratory mixing studies - J. Wu; L. Graham; S. Peacock; B. Nguyen; Y. Feng; M. Hurley; G. Short; D. Harris; W. Bruckard (Minerals Engineering, 2023)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

A missense variant of the porcine melanocortin-4 receptor (MC4R) gene is associated with fatness, growth, and feed intake traits - Kwan Suk Kim; Niels Larsen; Tom Short; Graham Plastow; Max F. Rothschild (Mammalian Genome, 2000)

Investigation of the retinol-binding protein 4 (RBP4) gene as a candidate gene for increased litter size in pigs - Max F. Rothschild; Lori Messer; Andy Day; Richard Wales; Tom Short; Olwen Southwood; Graham Plastow (Mammalian Genome, 2000)